The dynamic parameters of passive human at temporary demountable grandstands during exposure to lateral vibration - Yuan, Jian; He, Lin; Fan, Feng; Liu, Cong (Journal of Civil Engineering and Management, 2018)
Modelling the interaction between crowds and temporary demountable grandstands with identifying the human dynamic properties are challenges for structure optimal design. In this paper, for investigating and understanding the human and structural lateral dynamic features. A demountable grandstand was tested to obtain its model parameters firstly. Then it is tested at amplitudes between 0.16 m/s2 to 1.54 m/s2 with 75 random waves through a shaking table when occupied by twenty persons. Afterword a simplified two-degree of freedom lumped dynamic model of the joint human-structure system is reinterpreted. Utilizing the state-space model, the passive crowd dynamic parameters are obtained, based on root mean square accumulation error analysis. Statistical analysis of the predictive results concludes that seated crowd model damping ratio is 0.5, and the probable natural frequency is 2.0 Hz with the model mass ratio 0.7. For standing crowd model, the probable natural frequency is 1.5 Hz with the model mass damping ratio 0.4, and the model mass ratio is 0.7. It may have ability to serve as a reference value that can be utilized in vibration safety and serviceability assessment of TDGs, to estimate realistically the vibration response on the occasions when crowd are seated or standing.